The Right to Education for Women in Islam: Hak atas Pendidikan bagi Perempuan dalam Islam - Mehrabani, Rahmatullah; Obaid, Gheyasuddin (Indonesian Journal of Islamic Studies, 2025)
General Background: Islam places a high value on knowledge, making education a fundamental right and duty for all, regardless of gender. Specific Background: Historically, Muslim women played essential roles as educators and scholars, supported by Islamic teachings that promote learning. Knowledge Gap: However, in some Islamic societies today, especially in Afghanistan, women face restricted access to education due to social and political factors, despite Islamic encouragement. Aims: This research aims to reaffirm the right of women to education and work within the framework of Islamic jurisprudence and to propose appropriate educational models aligned with Sharia. Results: The findings show that Islam permits and, in some cases, obliges women to pursue religious and scientific knowledge, and allows work outside the home when necessary. Novelty: By referencing classical and contemporary Islamic sources, the study clarifies misconceptions and offers practical, religiously grounded solutions for women’s access to education. Implications: This research highlights the need for governments to create separate, safe, and Sharia-compliant educational environments for women, reinforcing their role in nurturing future generations within Islamic societies.Highlight : Education is a right and obligation for women in Islam, grounded in religious texts and scholarly consensus. Teaching both religious and natural sciences to women is essential for individual and societal development. Women's work outside the home is permissible in cases of necessity, while upholding Islamic principles. Keywords : Women, Education, Knowledge, Stratum, Work